2013
DOI: 10.1002/hrdq.21154
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Support for Action Learning in South Korean Organizations

Abstract: The purpose of this study was (1) to examine the impact of organizational support on employee learning and performance and (2) to elaborate on the context of organizational support for action learning in South Korean organizations. For this inquiry, two central questions were posed: What are employee reactions to organizational support for action learning? And what are key elements of organizational support for action learning? Framed by organizational support theory (OST), this study involved a mixed methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 74 publications
4
6
0
Order By: Relevance
“…In addition, performance evaluation and in-house global leadership programs greatly contributed to their advancement. Given research on organizational support for leadership, human resource practices, and working conditions (Carter et al, 2013;Cho and Egan, 2013;Kurtessis et al, 2017;Walsh, Fleming, & Enz, 2016), this study's findings have qualitatively confirmed the importance of organizational support for women CEOs' career success.…”
Section: Implications For Researchsupporting
confidence: 58%
“…In addition, performance evaluation and in-house global leadership programs greatly contributed to their advancement. Given research on organizational support for leadership, human resource practices, and working conditions (Carter et al, 2013;Cho and Egan, 2013;Kurtessis et al, 2017;Walsh, Fleming, & Enz, 2016), this study's findings have qualitatively confirmed the importance of organizational support for women CEOs' career success.…”
Section: Implications For Researchsupporting
confidence: 58%
“…As a result, I became the youngest team leader in the company. This female executive's testimonial implies the importance of organizational support, particularly supervisor support, on employee learning and performance (Cho and Egan, 2013).…”
Section: Implications For Practicementioning
confidence: 99%
“…In Volume 24 of HRDQ, Cho and Egan (), as well as Li, Gray, and Lockwood () presented innovative studies of workplace learning. Dachner, Saxten, Noe, and Keeton () described a novel approach to needs assessment in a rapidly changing environment.…”
Section: Conclusion and Insights For Authors Submitting To Hrdqmentioning
confidence: 99%